The assessment of the small farmer credit program in agricultural systems in Begnas Village Development Committee, Nepal - Singh, Bishnu Dayal; Boonjit Titapiwatanakun; Upasena, S. H.; Weber, Karl E.; Government of Japan (Bangkok : Asian Institute of Technology, 1993)
This study was an exploratory type and mainly focussed on the assessment of the Small Farmer Credit Program on Agricultural Systems. Desirable Socio-economic changes have occurred among the project beneficiaries. The income of the project beneficiaries have increased by 17.523 during the 9th year project period. The productivity of land has been increased significantly. Gross household income from different crops was found higher in the non-project participants group than in the project participants group. However, net farm income and income from livestock was higher among the project participants group. The most pressing problem in the project participants group area was soil moisture stress followed by s mall size of holding and fragmented land . Farmers were found well aware of soil degradation problems and following the conservation oriented practices. Both groups have followed almost similar soil conservation oriented practices. The income and productivity of land have been increased but the repayment rate of the SFDP has been found decreased. Income generatin g activities and social and community development programs were to be found not operated simultaneously. Project activities were focused more on income generatin g rather than on environmental conservation. Undoubtedly project has done a lot for the development of the area. It would be more effective if the program had been focussed on the sustainability of environmental conservation. Any project would be vital if income generating activities and en vironmental s ustainability were geared together while implementing the Project.
Thesis (M.Sc.) - Asian Institute of Technology, 1993
A thesis submitted in partial fulfillment of the requirement for the Degree of Master of Science.
Keywords: Agricultural credit -- Nepal